1990
DOI: 10.1017/s0950268800059380
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim resistance gene inShigella dysenteriae1 isolates obtained from widely scattered locations of Asia

Abstract: SUMMARYTrimethoprim-resistance genes of Shigella dysenteriae 1 strains, isolated from a different location of six different countries of Asia over a 5-year period were characterized by using three different dihydrofolate reductase (DHFR) gene probes. The trimethoprim-resistant (TMPR) strains hybridized only with the type

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
2
8
1
Order By: Relevance
“…Within a single serotype multiple patterns were observed, indicating their clonal heterogeneity. In a previous study, numerous plasmid patterns were found in S. dysenteriae type 1 isolated from scattered as well as defined geographical origins (6). It was also shown elsewhere that the core plasmids (140, 6, and 2 MDa) were present in both the epidemic and nonepidemic isolates of S. dysenteriae type 1, which correlated with the results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Within a single serotype multiple patterns were observed, indicating their clonal heterogeneity. In a previous study, numerous plasmid patterns were found in S. dysenteriae type 1 isolated from scattered as well as defined geographical origins (6). It was also shown elsewhere that the core plasmids (140, 6, and 2 MDa) were present in both the epidemic and nonepidemic isolates of S. dysenteriae type 1, which correlated with the results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that African and Asian strains of Shiga bacillus show multiple species of small cryptic plasmids [13,15]. The present study showed that, other than S. dysenteriae type 2 which usually contained a single cryptic plasmid, non-Shiga isolates contained 3-6 cryptic plasmids less than 10 MDa in size.…”
Section: Discussionsupporting
confidence: 47%
“…This plasmid is thought to be responsible for bacterial invasiveness [25]. The 6-0 MDa plasmid which characterizes Shiga bacillus [13,15,26] was not found in any non-Shiga isolates. It seems that the 6-0 MDa plasmid is truly serotype-specific of the Shiga bacillus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 analysed the plasmid profiles of strains of Shiga's bacillus from different geographical locations other than Africa. The major resist- $ Three isolates were from epidemics in rural Ethiopia.…”
Section: Discussionmentioning
confidence: 99%